Short-term results of the RAPID randomized trial of the legflow P aclitaxel-eluting balloon with supera stenting vs supera stenting alone for the treatment of interme diate and long superficial femoral artery lesions - Boer, Sanne W. de; Böckler, Dittmar; Dovzhanskiy, Dmitriy I. (Journal of endovascular therapy, 2017)
Purpose: To report a randomized trial comparing the Legflow paclitaxel-eluting balloon (PEB) + Supera stenting to Supera stenting alone in patients with intermediate to long superficial femoral artery (SFA) lesions. Methods: The multicenter RAPID trial (controlled-trials.com; identifier ISRCTN47846578) randomized (1:1) 160 patients (mean age 67 years; 102 men) with Rutherford category 2-6 ischemia to treatment with Legflow PEB + Supera stent or Supera stent alone in intermediate to long SFA lesions (mean lesion length 15.8±7.4 vs 15.8±7.6 cm, respectively). The efficacy outcome was primary patency, defined as freedom from restenosis on duplex ultrasound or angiography. Results: Baseline characteristics including the percentage of occlusions were similar between groups. In the intention-to-treat analysis, the estimated primary patency at 1 year was 68.3% (95% CI 56.7% to 79.9%) in the PEB + Supera group vs 62.0% (95% CI 49.1% to 74.9%) in the Supera group (p=0.900). Per-protocol analysis showed a 12-month primary patency estimate of 74.7% (95% CI 63.1% to 86.3%) in the PEB + Supera group vs 62.0% (95% CI 49.1% to 74.9%) in the control group (p=0.273). Secondary patency estimates at 12 months (per-protocol analysis) were 89.0% (95% CI 80.6% to 97.4%) vs 98.0% (95% CI 94.1% to 100%; p=0.484); the estimates for freedom from clinically driven target lesion revascularization (CD-TLR) were 83.0% (95% CI 72.8% to 93.2%) and 77.8% (95% CI 66.6% to 89.0%; p=0.277), respectively. Conclusion: The short-term results from the multicenter RAPID randomized controlled trial indicate that the Legflow PEB is safe and feasible for the treatment of intermediate to long SFA lesions. In this trial, at least 70% of the patients suffered an occlusion. The PEB group had higher rates of primary patency and freedom from CD-TLR, although there were no statistically significant differences vs controls.